Large Eddy Simulation of transitional flows in rotor/stator cavity - Tuliszka-Sznitko, E.; Zielinski, A.; Majchrowski, W. (Archives of Mechanics, 2009)
An algorithm for the Large Eddy Simulation, with subgrid modelling based on the spectral Chebyshev–Fourier approximation, is developed for the investigation of 3D turbulent and transitional non-isothermal flows within a rotor/stator cavity. In LES we use a version of the dynamic Smagorinsky eddy viscosity model in which the Smagorinsky coefficient at a given position x depends on the history of the flow along the fluid particle pathline. Computations are based on the efficient pseudo-spectral Chebyshev–Fourier method (S. Hugues, A. Randriamampianina, An improved projection scheme applied to pseudospectral methods for the incompressible Navier–Stokes equations, Int. J. Numer. Methods Fluids, 28, 501, 1998). To demonstrate the effectiveness of the proposed algorithm, computations were performed for the cavity of aspect ratio L=5 and results were compared favorably with the experimental data taken from literature.